Provisioning the High Country: A Distributional Analysis of Ground Stone Tools from the Colorado Front Range. (3rd July 2017) - Pelton, Spencer R.
Abstract : Prehistoric foragers living in the high elevations of the Colorado Front Range (CFR) transported ground stone tools at least 20 km from the CFR foothills to around 40 percent of sites in the subalpine forest and alpine tundra despite the sparse plant resources present in this region. This study is a distributional analysis that explains why there are so many ground stone tools in the CFR and how foragers developed strategies to efficiently utilize sparse high elevation plant resources. I draw expectations from the provisioning of place, which involves the efficient allocation of tools across space, and then test those expectations on a distributional data set of ground stone tools from the CFR. I conclude that foragers in the CFR practiced a generalist, bordering on intensive provisioning strategy in which a large number of sites were each provisioned with a small to moderate number of ground stone tools in order to most efficiently utilize a broad suite of plant resources, as opposed to a single plant resource staple. Although the CFR does not contain alpine villages like other high elevation regions in the North American West, it contains evidence for a distinct form of residential settlement characterized by many short-term campsites provisioned with the tools necessary to support intensive plant resource exploitation.